Association between age and access to immediate breast reconstruction in women undergoing mastectomy for breast cancer. Issue 5 (8th February 2017) - Jeevan, R; Browne, J P; Gulliver-Clarke, C; Pereira, J; Caddy, C M; van der Meulen, J H P; Cromwell, D A
Abstract: Background: National guidelines state that patients with breast cancer undergoing mastectomy in England should be offered immediate breast reconstruction (IR), unless precluded by their fitness for surgery or the need for adjuvant therapies. Methods: A national study investigated factors that influenced clinicians' decision to offer IR, and collected data on case mix, operative procedures and reconstructive decision-making among women with breast cancer having a mastectomy with or without IR in the English National Health Service between 1 January 2008 and 31 March 2009. Multivariable logistic regression was used to examine the relationship between whether or not women were offered IR and their characteristics (tumour burden, functional status, planned radiotherapy, planned chemotherapy, perioperative fitness, obesity, smoking status and age). Results: Of 13 225 women, 6458 (48·8 per cent) were offered IR. Among factors the guidelines highlighted as relevant to decision-making, the three most strongly associated with the likelihood of an offer were tumour burden, planned radiotherapy and performance status. Depending on the combination of their values, the probability of an IR offer ranged from 7·4 to 85·1 per cent. A regression model that included all available factors discriminated well between whether or not women were offered IR ( c -statistic 0·773), but revealed that increasing age was associated with a fall in the probability of an IR offer beyond that expected from older patients' tumour and co-morbidity characteristics. Conclusion: Clinicians are broadly following guidance on the offer of IR, except with respect to patients' age. Abstract : Age should not matter